2014
DOI: 10.1007/s10570-014-0413-1
|View full text |Cite
|
Sign up to set email alerts
|

Selective oxidation of cellulose catalyzed by NHPI/Co(OAc)2 using air as oxidant

Abstract: With NHPI/Co(OAc) 2 as catalyst and air as oxidant, carboxylic group functionalized cellulose was prepared by oxidation of cellulose in acetic acid. Fourier transform infrared spectroscopy was utilized to detect the generation of carboxylic group and the acid amount was determined by acid-base titration method. The present results revealed that C6 primary hydroxyl groups on glucose units were partly converted to carboxylic groups during the catalytic oxidation process. The degree of polymerization of oxidized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 34 publications
0
6
0
1
Order By: Relevance
“…[20][21][22][23][24] Herein, the preoxidation method was proposed to enhance the reactivity of cellulose. The hydroxymethyl groups are converted to carboxyl groups which act as catalytic active sites for both cellulose depolymerization during pretreatment and the subsequent hydrolysis of cellulose to glucose.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[20][21][22][23][24] Herein, the preoxidation method was proposed to enhance the reactivity of cellulose. The hydroxymethyl groups are converted to carboxyl groups which act as catalytic active sites for both cellulose depolymerization during pretreatment and the subsequent hydrolysis of cellulose to glucose.…”
Section: Introductionmentioning
confidence: 99%
“…Our research group and other researchers have reported that the hydroxymethyl groups on cellulose fibers can be selectively converted to carboxyl groups to improve the fiber properties and enlarge its application fields. [20][21][22][23][24] Herein, the preoxidation method was proposed to enhance the reactivity of cellulose. The hydroxymethyl groups are converted to carboxyl groups which act as catalytically active sites for both cellulose depolymerization during pretreatment and the subsequent hydrolysis of cellulose to glucose.…”
Section: Introductionmentioning
confidence: 99%
“…Завдяки м'якій окисній дії Оксону можна окиснювати альдегіди до карбонових кислот і естерів. ПІНОфталімід-N-оксирадикалгенерується in situ із N-гідроксисукциниміду та використовується в хімії як активуючий реагент для одержання карбонових кислот і як окисник для окиснення целюлози [7].…”
Section: вступunclassified
“…Representative instruments include an ultrasonic crusher (Jiang et al 2021), high-pressure homogenizer (Park et al 2019), and micro-jet nanoscale homogenizer, etc. The third method is to pretreat cellulose through sodium periodate (Sun et al 2015), TEMPO (De Castro et al 2018), nitrogen oxide, N-Hydroxyphthalimide (NHPI), and other oxidation systems (Zhou et al 2014) to change the functional groups of cellulose, thus achieving specific good physical and chemical properties. After such chemical treatments, nanocellulose with different chemical properties can be obtained through mechanical treatment.…”
Section: Introductionmentioning
confidence: 99%